African migrations - Adi, Hakim (Wayland Hove, 1994)
The book Africans migrations by Hakim Adi, published in 1994 by Wayland Publishers. This 48-page book provides an overview of significant migrations from Africa throughout history, from ancient times to the present day. It is illustrated with color and black-and-white artwork and maps to support the text.